Carte postale photographique et balnéarisation des villes littorales : le cas de Royan (1895-1920) - Benjamin Caillaud (Confins)
Between 1895 and 1920, the city of Royan’s seaside economy experienced a new boom, making it one of the most visited resorts on the French Atlantic coast. During the same period, a new communication medium enjoyed massive popular success: postcards, illustrated with photographs. Proclaimed actor of the seaside economy, the photographer and editor Fernand Braun established himself as an influential player in the postcard publication business while his competition conformed to a standard visual offering of the main heritage attractions. Mass-distributed in the postcard format, Braun’s shots were also used by the national publishing houses for illustrated books. Using a visual rhetoric that is specific to the postcard, Fernand Braun “invents” the landscape of Royan’s shores and spreads a modern aesthetic of the Atlantic coastline.